Enantiomers of 4‐aminopentanoic acid act as false GABAergic neurotransmitters and impact mouse behavior. Issue 5 (2nd August 2021) - Wawro, Adam M.; Gajera, Chandresh R.; Baker, Steven A.; Leśniak, Robert K.; Montine, Kathleen S.; Fischer, Curt R.; Saw, Nay L.; Shamloo, Mehrdad; Montine, Thomas J.
Abstract : Abstract: Imbalance in the metabolic pathway linking excitatory and inhibitory neurotransmission has been implicated in multiple psychiatric and neurologic disorders. Recently, we described enantiomer‐specific effects of 2‐methylglutamate, which is not decarboxylated to the corresponding methyl analogue of gamma‐aminobutyric acid (GABA): 4‐aminopentanoic acid (4APA). Here, we tested the hypothesis that 4APA also has enantiomer‐specific actions in brain. Mouse cerebral synaptosome uptake (nmol/mg protein over 30 min) of ( R )‐4APA or ( S )‐4APA was time and temperature dependent; however, the R enantiomer had greater uptake, reduction of endogenous GABA concentration, and release following membrane depolarization than did the S enantiomer. ( S )‐4APA exhibited some weak agonist (GABAA α4β3δ, GABAA α5β2γ2, and GABAB B1/B2) and antagonist (GABAA α6β2γ2) activity while ( R )‐4APA showed weak agonist activity only with GABAA α5β2γ2. Both 4APA enantiomers (100 mg/kg IP) were detected in mouse brain 10 min after injection, and by 1 hr had reached concentrations that were stable over 6 hr; both enantiomers were cleared rapidly from mouse serum over 6 hr. Two‐month‐old mice had no mortality following 100–900 mg/kg IP of each 4APA enantiomer but did have similar dose‐dependent reduction in distance moved in a novel cage. Neither enantiomer at 30 or 100 mg/kg impacted outcomes in 23 measures of well‐being, activity chamber, or withdrawal from hot plate. Our results suggest that enantiomers of 4APA are active in mouse brain, and that ( R )‐4APA may act as a novel false neurotransmitter of GABA. Future work will focus on disease models and on possible applications as neuroimaging agents. Abstract : Enantiomers of 4‐aminopentanoic acid (4APA) are metabolically restricted methylated forms of GABA. (R)‐ and (S)‐4APA were taken up by mouse cerebral synaptosomes (left) in a time‐ and temperature‐dependent manner, partially displaced GABA, and were released upon membrane depolarization with high concentration potassium cation. However, both enantiomers had very limited interaction with GABA or glutamate receptors. When injected into mice (right), these false GABAergic neurotransmitters were readily taken up and retained in brain and differentially impacted mouse behavior. Enantiomers of 4APA may have applications as therapeutics or molecular imaging agents.